Arbitrage and the Savings Behavior of State Governments - Metcalf, Gilbert E. (The Review of Economics and Statistics, 1990)
The federal tax code creates strong incentives for tax arbitrage on the part of state governments. This arbitrage activity is illegal and previous research has typically assumed that the constraint against arbitrage activity is binding. This paper explicitly tests this proposition by considering whether financial asset holdings increase as the yield spread between taxable and tax exempt securities rises. Using a data set on 40 state governments over a seven year period, I find that there is a significant response to changes in the yield spread. One implication of these results is that the Tax Reform Act of 1986, which made even greater efforts to curb arbitrage activity, is likely to be ineffective. Copyright 1990 by MIT Press.